Scale of Teacher efficacy in classroom diversity (TESCD): A validation study. - Kitsantas, Anastasia (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The purpose of the present study was to validate the Teacher Efficacy Scale for Classroom Diversity (TESCD). This scale was developed to measure preservice teachers’ self-efficacy beliefs in their capability to teach students from diverse backgrounds. Four hundred and seventeen (N=417) preservice teachers participated in the study. Data analyses revealed that overall the TESCD has a good construct and concurrent validity and reliability. Recommendations are made for using this scale to examine preservice teachers’ efficacy beliefs in teaching diverse student populations.